Jeux parodiques munoliens entre autobiographie et autofiction à l’heure d’«une autre Belgique» - Moreels, Isabelle (2018)
The numerous parodic discrepancies which punctuate ‘Histoire exécrable d’un héros brabançon’ (1982) by Jean Muno show us, five years after the initial creation of the neologism ‘auto-fiction’ by Serge Doubrovsky, a background ensemble of questions about the autobiographical pact defined ten years earlier by Philippe Lejeune. Yet this desire, manifested by a major novelist of Belgian letters about the French language in the second half of the 20th century, to free oneself from the restrictions of the autobiographical genre is part of the empowerment process of the Belgian francophone literary field. Indeed, the very marked national anchoring of this narrative, both historically and linguistically, illustrates the identifying affirmation claimed by the francophone Belgian literature through the concept of ‘belgitude’ at the turning point of the 1980s.